The Assessment of Congenital Laryngeal Lesions in Infants with Stridor - Fulya Özer; Cem Özer; Fatma Çaylaklı; Alper Nabi Erkan (Çocuk Dergisi)
Objective: In neonatal stridor, various conditions can be responsible as well as laryngomalacia. These conditions can be quite rare and the treatment of these diseases could be complicated. The purpose of this study is to identify the laryngeal pathologies and to discuss our approach in infants with chronic stridor. Methods: The hospital charts of infants with stridor undergoing rigid laryngotracheobronchoscopy in our hospital in 2018-2022 were retrospectively reviewed. Results: 107 children were enrolled to the study. The most frequent diagnosis was laryngomalacia (isolated and seen with secondary airway lesions (SALs)) (74 patients, 69.1%). 10 patients (9.3 %) had subglottic stenosis which caused stridor or dyspnea. Regarding other laryngeal lesions, in 8 patients (7.47 %) the diagnosis was laryngeal edema and 8 patients (7.47 %) had tracheomalacia. SALs which occurred with laryngomalacia were seen in 16 patients of our series (14.9 % of all cases). Surgery was performed in 11 of patients. Stridor was resolved in % 80 of laryngomalacia patients at about 2 years of age with only follow up. Conclusions: In neonatal stridor, various conditions can be responsible as well as laryngomalacia. Referral of infant to otorhinolaryngologists and examination with flexible and rigid endoscopy is necessary for the assessment of stridor. The examination of the airway with the rigid endoscopy under general anesthesia without intubation on operating room with the cooperation of the anesthesiologist may provide the surgical intervention together with simultaneous inspection especially in the patients with severe stridor and systemic diseases.